HUBUNGAN DUKUNGAN SUAMI TERHADAP PEMBERIAN ASI EKSKLUSIF PADA BAYI DI WILAYAH KERJA PUSKESMAS ALALAK SELATAN BANJARMASIN TAHUN 2019 - Norlina, Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Breast milk (ASI) is the first and foremost meal for newborns and is best and natural, contains all nutrients according to the needs for optimal growth and development of babies. The problem with exclusive breastfeeding is the low understanding of mothers, families and communities about breastfeeding. Motivation of mothers to give exclusive breastfeeding will rise if they gain confidence and get information about correct breastfeeding. Family support, especially husband, is very important, where the husband is very decisive whether or not the mother in providing breast milk (ASI) to her baby. A strong urge from the husband and a good explanation makes the mother want to give breast milk to her baby. This study aims to determine the relationship of husband's support to exclusive breastfeeding in infants in the Alalak Selatan Community Health Center Banjarmasin. This type of research is an Analytical Survey. Samples were taken by accidental sampling technique, with a total sample of 35 respondents. The results showed that the results of the Spearman Rho satistic test showed that there was a relationship between husband's support for exclusive breastfeeding in infants at the Alalak Selatan Health Center in Banjarmasin. Suggestions for Puskesmas to further improve public health education about exclusive breastfeeding for infants through health workers is to further optimize socialization in posyandu on exclusive breastfeeding especially for pregnant women and nursing mothers in an effort to increase the coverage of Exclusive ASI programs for infants, and for husbands to support wife by accompanying his wife when giving breast milk to her baby so that the wife feels calm and the husband is actively involved in all activities related to the baby. Keywords: Husband Support, Exclusive Breastfeeding